2022
DOI: 10.3390/jpm12060972
|View full text |Cite
|
Sign up to set email alerts
|

Sex Difference in the Associations among Obesity-Related Indices with Incident Hypertension in a Large Taiwanese Population Follow-Up Study

Abstract: Hypertension is a major risk factor for stroke, atherosclerosis, and other cardiovascular diseases, and obesity is a major risk factor for hypertension. The aim of this longitudinal study was to investigate sex differences in the correlations among obesity-related indices and incident hypertension in a large Taiwanese cohort. We included 21,466 enrollees in the Taiwan Biobank and followed them for 4 years. Of the 21,466 patients enrolled in this study, 6899 (mean age, 49.6 ± 10.9 years) were male and 14,567 (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 56 publications
(64 reference statements)
1
13
0
Order By: Relevance
“…Based on office BP, the global prevalence of hypertension was estimated to be 1.13 billion in 2015 5 . Hypertension is a major risk factor for stroke, atherosclerosis, and other cardiovascular diseases, and obesity is a major risk factor for hypertension 47 . On the other hand, patients with hypertension are also frequently overweight or obese presenting a vicious circle, in which weight gain progressively increases as a consequence of hypertension and it also further aggravates the severity of the BP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on office BP, the global prevalence of hypertension was estimated to be 1.13 billion in 2015 5 . Hypertension is a major risk factor for stroke, atherosclerosis, and other cardiovascular diseases, and obesity is a major risk factor for hypertension 47 . On the other hand, patients with hypertension are also frequently overweight or obese presenting a vicious circle, in which weight gain progressively increases as a consequence of hypertension and it also further aggravates the severity of the BP.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive weight gain is associated with hypertension. However, the magnitude and the direction of the association tend to differ on the level of economic development, sex, and race 47,49 . Women tend to have a higher proportion of body fat stored in subcutaneous rather than visceral adipose tissue because of the differences in body composition between men and women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity can be evaluated using a variety of indices, including body mass index (BMI) [17], waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), lipid accumulation product (LAP), body roundness index (BRI) [18], conicity index (CI) [19], visceral adiposity index (VAI) [20], body adiposity index (BAI) [21], abdominal volume index (AVI) [22], and body shape index (ABSI) [23]. Quantifying obesity using these indices can help to evaluate their relationships with other health problems, and we previously identified associations between these obesity indices with fatty liver [24], albuminuria, advanced kidney disease [25], lung function [26], osteoporosis [27], hypertension [28], peripheral artery disease [29], and dementia [30].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies revealed that these obesity-related indices are predictors of hypertension [ 11 , 12 , 13 ]. Our recent research revealed that these obesity indices were associated with fatty liver [ 14 ], albuminuria, advanced kidney disease [ 15 ], lung function [ 16 ], osteoporosis [ 17 ], hypertension [ 18 ], peripheral artery disease [ 19 ], and dementia [ 20 ]. Moreover, although both overweight and underweight have been associated with osteoporosis [ 21 ], few studies have explored the relationship between osteoporosis and indices related to obesity.…”
Section: Introductionmentioning
confidence: 99%